Efektivitas Pemberian Sari Kacang Hijau dan Buah Naga Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil dengan Anemia di Klinik Aulia Medika Citeureup Kabupaten Bogor Tahun 2024 - Sindi Rahayu; Sri Kubillawati; Eka Maulana Nurzannah; Imelda Diana Marsilia (Jurnal Ners, 2025)
Anemia in pregnant women occurs due to increased nutritional needs and the process of hemodilution which peaks at 32 weeks of gestation. Anemia that is not treated immediately can have a negative impact on the mother and fetus. This study aims to determine the effect of giving mung bean and dragon fruit juice. The method used in this research is quantitative descriptive with Quasy Experiment research design and Two Group Pretest-Posttest Design approach, the statistical test used is T-Dependent Test if the data is normally distributed, but if the data is not normally distributed then it is done using Wilcoxon Test. The population in this study were 44 pregnant women, with a sample of 16 pregnant women who experienced anemia. The sampling technique in this study was Accidental Sampling. The results showed that the administration of mung bean juice and dragon fruit both had an effect in increasing the hemoglobin levels of pregnant women with a P-Value of 0.000 (α <0.05), and the mean of the mung bean juice intervention was 0.062 gr/dl greater than the mean of the dragon fruit intervention which means that the administration of mung bean juice is slightly more effective than dragon fruit to increase hemoglobin levels in pregnant women with anemia.